Effect of naked barley enrichment on the quality and nutritional characteristics of bread – Part I. The effect on wheat bread - Pejcz, Ewa; Wojciechowicz- Budzisz, Agata; Gil, Zygmunt; Czaja, Anna; Spychaj, Radosław (Engineering Sciences And Technologies, 2016)
Barley is gaining more interest due to its nutritional value, especially because of the dietary fibre content and the presence of non-starch polysaccharides Hull-less barley is a rich source of soluble and insoluble dietary fibre providing beneficial non-starch polysaccharides, especially β-glucans. The effects of different barley wholemeal share in wheat bread and different dough preparation methods on the quality of bread and its nutritional composition were investigated. Barley incorporation to wheat bread improved its nutritional quality by increasing the dietary fibre, β-glucans and arabinoxylans content. However, high barley concentration led to decrease in loaf volume and overall acceptability and changes in bread’s crumb and crust colour. Bread production method strongly influenced its quality and nutritional composition. Barley sourdough fermentation comparing to direct barley wholemeal incorporation allowed to obtain more acceptable products of higher nutritional quality
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 2 (21), s. 38-45
Keywords: hull-less barley; wheat bread; sourdough; dietary fibre; β-glucans; non-starch polysaccharides; jęczmień nagoziarnowy; pieczywo pszenne; zakwas; błonnik pokarmowy; β-glukany; polisacharydy nieskrobiowe